(untitled) (JED (Jurnal Etika Demokrasi), 2022)
The authority of Panglima Laot is still generally explained in Aceh Qanun Number 10 of 2008 concerning Customary Institutions, this causes an unclear, not detailed, and not strictly or even the occurrence of legal vacuum in some disputes because there is no legislation that regulates it. Therefore, regulations and guidelines, namely Qanuns are needed at the district level regarding the implementation of customary management of coastal sea rights in areas in Bireuen district so that the rules used as benchmarks in law enforcement are clear. We know that there are no detailed codified rules regarding the authority Panglima Laot in Bireuen District so that it does not provide legal guarantees for the community